Structures, functions, and syntheses of glycero-glycophospholipids - Osawa, Tsukiho; Fujikawa, Kohki; Shimamoto, Keiko (Frontiers in Chemistry, 2024)
Biological membranes consist of integral and peripheral protein-associated lipid bilayers. Although constituent lipids vary among cells, membrane lipids are mainly classified as phospholipids, glycolipids, and sterols. Phospholipids are further divided into glycerophospholipids and sphingophospholipids, whereas glycolipids are further classified as glyceroglycolipids and sphingoglycolipids. Both glycerophospholipids and glyceroglycolipids contain diacylglycerol as the common backbone, but their head groups differ. Most glycerolipids have polar head groups containing phosphate esters or sugar moieties. However, trace components termed glycero-glycophospholipids, each possessing both a phosphate ester and a sugar moiety, exist in membranes. Recently, the unique biological activities of glycero-glycophospholipids have attracted considerable attention. In this review, we describe the structure, distribution, function, biosynthesis, and chemical synthetic approaches of representative glycero-glycophospholipids—phosphatidylglucoside (PtdGlc) and enterobacterial common antigen (ECA). In addition, we introduce our recent studies on the rare glycero-glyco“pyrophospho”lipid, membrane protein integrase (MPIase), which is involved in protein translocation across biomembranes.